Aggressiveness Traits as Predictive Factors for the Components of the Wellbeing of Young People - Artur A. Rean; Andrey O. Shevchenko; Alexey A. Stavtsev; Ivan A. Konovalov; Roman G. Kuzmin (Национальный психологический журнал)
Background. Aggression and aggressiveness as properties of personality are certainly among the most destructive phenomena. As young people are an important social group in the structure of society, the direction of development greatly depends on them. It becomes topical to study the relationship between the parameters of psychological well-being and aggression in the personality structure of student youth. Objective. The goal is to study the relationship of aggression with life satisfaction, self-esteem and self-efficacy of student youth in the Russian Federation. Methods. Bass-Perry aggression questionnaire, E. Diener’s Life Satisfaction questionnaire, Self-esteem questionnaire — Self-esteem. Rosenberg Self-esteem Scale (RSE). Correlation analysis and linear regression were used in the processing of the obtained results. Study Participants. 1398 respondents participated, mean subject age 20.2 (min. — 17, max. — 30): 1033 female subjects and 365 male subjects. Results. Upon analyzing the general patterns of linear regression and correlation, it was found that not all scales have similar trends: in some cases the relationships between “Life Satisfaction”, “Self-Esteem” and “Self-Efficacy” and aggressiveness scales are non-linear. It was found that the influence of aggressiveness scales on level-groups — “Life Satisfaction”, “Self-esteem” and “Self-efficacy”, are not equivalent to the results of general trends. Thus, the general pattern was that “Hostility” was a negative predictor of all three criteria of personality well-being: self-esteem, self-efficacy and life satisfaction. Regression analysis showed a U-shaped relationship between the scale “Physical Aggression” and Self-Efficacy. “Verbal aggression” is a significant predictor for low scores of Self-esteem and Self-efficacy. Conclusions. “Hostility” is a universal predictor (negative), in almost all cases and level-groups of well-being. “Verbal aggression” can be a positive predictor of “Self-Esteem” growth, only in the group of subjects with low self-efficacy, also it can act as a predictor of self-efficacy growth in the group of subjects with low self-efficacy values. “Physical aggression” is a significant predictor in the groups with high and low values of self-efficacy. The revealed patterns demonstrate the complexity of aggression. In addition, in certain cases, manifestations of aggression can be an effective mechanism of imaginary adaptation of the personality, however, in the long term, this overlaps the possibility of full systemic adaptation for the subject.